Discussion of the new economic world order - Helmut Hesse (Intereconomics, 1976)
It is difficult to know what to make of the present discussion about a New International Economic Order although it is certainly lively enough. Few observers can be able to point out the various levels at which arguments are bandied. Hardly anybody can distinguish a clear pattern in the variety and diversity of assertion and counter-assertion, of proposal and counter-proposal. It is often not even known how comprehensive and far-reaching the demands for a New Order are in reality. It would therefore seem to be a sensible undertaking to try to trace the structure of the discussion and make it hereby more intelligible.
Keywords: 330; New International Order